Analisis Nilai Tambah dan Kelayakan Non Finansial Minuman Teh Celup Kahwa Cassia Vera (Studi Kasus CV. Tiga Berlian) - Ruri Wijayanti; Dewi Arziyah; Malse Anggia (Agricultural Faculty, 2022)
West Sumatra is one of the coffee-producing areas. Product development is not only from the seeds but the leaves have also been used in the form of processed drinks known as kawa (leaf kawa) drinks. The high benefits of cassia vera which are supported by its potential and development prospects are good opportunities, coupled with the application of post-harvest technology, it can make the selling value of a product more value-added. The objectives of the research were: to analyze the added value of the Kahwa Casia vera tea bag industry, to analyze the non-financial feasibility of the Kahwa Casia vera tea bag industry, and to calculate the Break-Even Point (BEP) value of the Kahwa Casia vera tea bag industry. The research method used is a case study. The data collection process was carried out through observation, surveys, and interviews. The types of data needed in this research are qualitative data and quantitative data. The results showed that the Kahwa Casia vera tea beverage business provided an increase in added value for the Kahwa Casia vera tea beverage business per kg of 73.65% of the product value. Based on the analysis of non-financial aspects which include marketing plans, engineering, and technology plans, as well as organizational and management plans, the Kahwa Casia Vera Tea beverage business is considered feasible to run. Then the Kahwa Casia vera tea beverage business is above its break-even point (BEP) in rupiah of IDR 95,903,577, while the BEP in units is 2,559 units.